Accelerating sustainable and economic development via industrial energy cooperation and shared services – A case study for three European countries. (January 2022) - Mainar-Toledo, M.D.; Castan, M.A.; Millán, G.; Rodin, V.; Kollmann, A.; Peccianti, F.; Annunziata, E.; Rizzi, F.; Frey, M.; Iannone, F.; Zaldua, M.; Kuittinen, H.
Abstract: The European industry sector is responsible for about one-third of the EU's total energy consumption and process-related Greenhouse Gas emissions, which makes it a central factor in the EU's climate and energy strategies. Energy cooperation, i.e., the mutualised generation, use and/or acquisition of energy by at least two companies, has the potential of significantly supporting the successful achievement of these strategies. This paper presents a concept for moving from a single-company sustainable energy intervention approach to cooperative sustainable energy solutions within the framework of industrial parks. Technical, economic, regulatory, organizational, and social barriers for energy-efficient park design and operation on all levels and instruments to overcome them have been systematically analysed, taking correlation of solutions, and park-specific requirements into account, thus providing a holistic workflow. First results show that technical and economic attractiveness, and an enabling legal and policy context, are not always enough. For promising energy cooperation solutions to flourish, cultural, organizational, social, and behavioural factors also play a significant role. Furthermore, findings show that external facilitators are helpful to pool efforts to achieve greater engagement. Highlights: Systematic assessment of barriers to energy cooperation and instruments to overcome them. Highlighting the role of park managers as key facilitators of energy cooperation. Assessment of feasibility studies based on key performance indicators. Proposes a replicable strategy to identify energy cooperation opportunities at the industrial park level. Integration of the findings in an easy-to-use decision-making tool.